Safety in Mixed Martial Arts: a 7-Year Review of Cancelled MMA Bouts in Calgary, Alberta, During the Pre-bout Medical Examination Period - Gwynn Curran-Sills (SpringerOpen, 2018)
Abstract Background Presently, there is no literature that examines the reasons for the cancellation of amateur or professional mixed martial arts (MMA) bouts. The purpose of this study was to review the circumstances that lead to the cancellation of MMA bouts by Calgary ringside physicians during the pre-bout examination period and to identify any emerging patterns that may guide the regulatoin of this sport. Methods The case-series  was constructed from the Calgary Combative Sports Commission pre-bout examination records and the medical records submitted by each athlete from January 2010 to December 2016. Results Cancelled bouts in the pre-bout examination periods represented 5.4% of all MMA bouts in Calgary. A total of 25 reasons lead to bout cancellation and included the following: failure to obtain required neuroimaging (28.0%), neuroimaging abnormalities (24.0%), incomplete routine screening investigations (16.0%), exceeding maximum weight differential between the two athletes (16.0%), injury in the pre-competition period (8.0%), dehydration (4.0%), and ECG abnormalities (4.0%). The abnormalities on neuroimaging (n of 6) included the following: post traumatic gliosis on MRI (n = 1, 16.7%), flares diffusely and findings consistent with microhemorrhage on MRI (n = 1, 16.7%), chronic orbital fracture with fat pad extrusion on CT (n = 2, 33.3%), lacunar infarct on MRI (1), and unspecified MRI abnormality (n = 1, 16.7%). Twenty-two athletes had bouts cancelled and of these three athletes had their bouts stopped for two reasons. Conclusions The following recommendations are presented and include: the creation of guidelines regarding pre- and post-bout neuroimaging, the implementation of industry-wide minimum medical screening standards, the adoption of a longitudinal approach to weight monitoring, the development of competent ringside physician groups, and active oversight by the Combative Sports Commission during the matchmaking process.